Hadrian’s Villa: A Source of Inspiration for Neoclassical Russia? - Ruggero, Cristina (Actual Problems of Theory and History of Art, 2020)
In her ambitious plans to renovate Russia, on the example of other European courts, the Tsarina Catherine the Great (1762–1796) was aware of the important role played by antiquity as a model of reference, of which Rome was in the lead. Among the many monuments, Hadrian’s Villa (117–138 C.E.) representedan authoritative example for the richness and variety of its buildings. The site was also discussed in many 18th-century treatises as worthy to be studied and echoed in the coeval projects. The essay tries to answer how Hadrian’s Villa could have been a source of inspiration for Neoclassical Russia. This imperial site experienced a broad and in-depth reception all over the world, mostly in the 18th and 19th centuries. Here an attempt was made to retrace how the acquisition of knowledge about Hadrian’s Villa on Russian soil and the appropriation of architectural motifs did not take place directly through architects from this country but thanks to the mediation of foreign artists. Moreover, in Russia, there was also a strong echo of Renaissance architecture and Palladianism, or of the younger Neoclassicism combined with an eclectic behaviour towards other art movements and cultures like the neo-Gothic and Chinese, which were similarly the result of assimilations through foreign influences. These are all reasons and explanations why it is more difficult in Russia than elsewhere to find a direct quotation of ancient buildings. The reception of Hadrian’s Villa took place in a subtle way, often mediated by artists able to insert its distinctive features in diverse projects. The most famousis by Charles-Louis Clérisseau who submitted a design for an imperial palace — even if the original request was for a garden pavilion – where he condensed the more peculiar features of Roman architecture, of which Hadrian’s Villa seems to be the main source of reference.
Keywords: Hadrian’s Villa in Tivoli; Diocletian’s Palace in Split; Grand Tour; Catherine the Great; Charles-Louis Clérisseau; Giacomo Quarenghi; Charles de Wailly; John Soane; Charles Cameron